Hubungan Komorbid Hipertensi dengan Gejala Long Covid-19: Studi Pada Pasien Covid-19 yang Pernah di Rawat Inap di RSUD Al-Ihsan Provinsi Jawa Barat dan RSUD Cideres Majalengka - Althaafvashti Trixie Niadi; Lelly Yuniarti; Abdul Hadi Hassan (UNISBA Press, 2023)
Abstract. Long COVID-19 is a prolonged symptom in patients who have recovered from COVID-19 which incidence increases along with the increasing cases of COVID-19. One of the risk factors for long COVID-19 is comorbid hypertension. This study aimed to discover the relationship between comorbid hypertension and long COVID-19 symptoms. The subjects of this study were COVID-19 inpatients at Al-Ihsan and Cideres Hospital from December 2020–February 2022. This analytical study used a case-control design conducted from December 2021–December 2022. Primary data was gained through interviews and questionnaires. Secondary data was acquired from medical records. The total subjects were 120 patients (65 subjects as cases and 55 subjects as controls) who met the inclusion criteria and were selected using the purposive sampling technique. The results showed that most COVID-19 patients aged 56–65 years and the number was comparable between men and women, most long COVID-19 patients aged 56–65 years and are female, more subjects did not have comorbid hypertension (54.2%), more subjects experienced long COVID- 19 symptoms (54.2%), and the most common long COVID-19 symptoms were fatigue, coughing, and dyspnea. Most COVID-19 patients with comorbid hypertension (41.7%) experienced long COVID-19 symptoms, while most COVID- 19 patients without comorbid hypertension did not experience long COVID-19 symptoms. The conclusion of this study, based on bivariate analysis using Fisher’s exact test with a 95% confidence level, is that there is a correlation between comorbid hypertension and long COVID-19 symptoms (p<0.05). COVID-19 patients with comorbid hypertension are more at risk of experiencing long COVID-19 symptoms. Abstrak. Long COVID-19 merupakan gejala berkepanjangan pada pasien yang telah pulih dari COVID-19 yang kejadiannya meningkat seiring dengan meningkatnya kasus COVID-19. Salah satu faktor risiko terjadinya long COVID-19 adalah komorbid hipertensi. Tujuan penelitian ini adalah mengetahui hubungan komorbid hipertensi dengan gejala long COVID-19. Subjek penelitian adalah pasien COVID- 19 yang pernah dirawat inap di RSUD Al-Ihsan dan Cideres pada Desember 2020– Februari 2021. Penelitian analitis ini menggunakan desain case-control dan dilaksanakan pada Desember 2021–Desember 2022. Data primer diperoleh melalui wawancara dan pengisian kuesioner serta data sekunder diperoleh dari rekam medis. Total subjek penelitian berjumlah 120 pasien yaitu didapatkan 65 kasus dan 55 kontrol yang memenuhi kriteria inklusi dan dipilih dengan teknik purposive sampling. Hasil penelitian menunjukkan bahwa pasien COVID-19 paling banyak berusia 56–65 tahun dan sebanding jumlahnya antara laki-laki dan perempuan, pasien long COVID-19 paling banyak berusia 56–65 tahun dan lebih banyak yang berjenis kelamin perempuan, lebih banyak pasien COVID-19 yang tidak memiliki komorbid hipertensi (54,2%), lebih banyak pasien COVID-19 yang mengalami gejala long COVID-19 (54,2%), dan gejala long COVID-19 yang paling sering dialami adalah fatigue, batuk, dan dyspnea. Sebagian besar pasien COVID-19 dengan komorbid hipertensi (41,7%) mengalami gejala long COVID-19, sedangkan sebagian besar pasien COVID-19 tanpa komorbid hipertensi tidak mengalami gejala long COVID- 19. Kesimpulan penelitian ini, berdasarkan analisis bivariat menggunakan Fisher’s exact test dengan tingkat kepercayaan 95%, adalah terdapat hubungan antara komorbid hipertensi dan gejala long COVID-19 (p<0,05). Pasien COVID-19 dengan komorbid hipertensi lebih berisiko mengalami gejala long COVID-19.